Cutting Edge: SARS-CoV-2 Infection Induces Robust Germinal Center Activity in the Human Tonsil - Tan, Hyon-Xhi; Wragg, Kathleen M; Kelly, Hannah G; Esterbauer, Robyn; Dixon, Benjamin J; Lau, Jillian S Y; Flanagan, Katie L; van de Sandt, Carolien E; Kedzierska, Katherine; McMahon, James H; Wheatley, Adam K; Juno, Jennifer A; et al. (The Journal of immunology (1950), 2022)
Understanding the generation of immunity to SARS-CoV-2 in lymphoid tissues draining the site of infection has implications for immunity to SARS-CoV-2. We performed tonsil biopsies under local anesthesia in 19 subjects who had recovered from SARS-CoV-2 infection 24-225 d previously. The biopsies yielded >3 million cells for flow cytometric analysis in 17 subjects. Total and SARS-CoV-2 spike-specific germinal center B cells, and T follicular helper cells, were readily detectable in human tonsils early after SARS-CoV-2 infection, as assessed by flow cytometry. Responses were higher in samples within 2 mo of infection but still detectable in some subjects out to 7 mo following infection. We conclude the tonsils are a secondary lymphoid organ that develop germinal center responses to SARS-CoV-2 infection and could play a role in the long-term development of immunity.